Caring for nature: what science and economics can't teach us but religion can - Rolston, Holmes, 1932-2025, author; White Horse Press, publisher (Colorado State University. Libraries, 2006)
Neither ecologists nor economists can teach us what we most need to know about nature: how to value it. The Hebrew prophets claimed that there can be no intelligent human ecology except as people learn to use land justly and charitably. Lands do not flow with milk and honey for all unless and until justice rolls down like waters. What kind of planet ought we humans wish to have? One we resourcefully manage for our benefits? Or one we hold in loving care? Science and economics can't teach us that; perhaps religion and ethics can.
Keywords: caring for creation; sustainable biosphere; sustainable development; human ecology; environmental justice; religion; ecology